2020
DOI: 10.1080/19932820.2020.1846861
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of social media ‘detoxification’ in university students

Abstract: The multiplication of social networking sites has led to increased frequency of use among young adults. While the association with mental wellbeing is still controversial, high levels of social media use were correlated with problematic behaviours, low self-esteem and depressive symptoms. 'Social Media Detoxification' (Detox) is the term used to describe voluntary attempts at reducing or stopping social media use to improve wellbeing. We conducted a pilot study to explore the characteristics of social media de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
(30 reference statements)
2
13
0
2
Order By: Relevance
“…In accordance with digital detox, social media detoxification has recently attracted scientific interest (Keles et al, 2020 ; Booker et al, 2018 ; El-Khoury et al, 2021 ). There are several benefits to detoxification, including enhanced mental wellbeing, social connections, and heightened productivity (Osterberg, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with digital detox, social media detoxification has recently attracted scientific interest (Keles et al, 2020 ; Booker et al, 2018 ; El-Khoury et al, 2021 ). There are several benefits to detoxification, including enhanced mental wellbeing, social connections, and heightened productivity (Osterberg, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Booker et al, 2018 ) discovered that among teenagers who use the Internet, social media profiles may have a detrimental influence on well-being later in adolescence and maybe into adulthood. Studying with 68 university students, El-Khoury et al ( 2021 ), during and after the detoxification period, the majority of students reported improved moods, reduced anxiety, and better sleep. What it means is that university students understand and employ “social media detoxification” to control their social media use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also important to consider weaknesses of a traditional common approach to prohibit or ban social media use for excessive users. Based on dual–system theories, this full stop strategy may only strengthen impulsive behavior as illustrated by recent experimental studies on social media abstinence (El‐Khoury et al, 2021; Franks et al, 2018; Przybylski et al, 2021; Wood & Muñoz, 2021). Yet, little is known about how to change implicit associations in the long term (Friese et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Los síntomas depresivos y la depresión fueron uno de los impactos psicológicos mayormente mencionados y citados en las investigaciones revisadas, lo anterior se puede deber a que las personas que reciben bajo apoyo social en la vida real, son propensas a aumentar el uso de redes sociales (Brailovskaia et al, 2018), así mismo las redes sociales pudieran generar problemas de regulación emocional (Rasmussen et al, 2020), al ver que otras personas tienen una vida más interesante que la nuestra, puede generar una dolorosa y profunda envidia a través de la comparación de las diversas realidades, haciendo que las personas presenten una bajos niveles de satisfacción con la vida (Balouch et al, 2019;Wang et al, 2019), repercutiendo negativamente en nuestra autoestima (Leung et al, 2021) y generando sentimientos de soledad y vacío (Zhang et al, 2020). La ansiedad puede estar asociada a la incapacidad de las personas de desconectarse de los medios digitales generando inclusive síntomas de abstinencia si es que no logran estar al tanto de lo que acontece en esta realidad virtual (El-Khoury et al, 2021), además ese miedo de perderse algo que está ocurriendo en las redes puede llevar al síndrome FOMO (Leung et al, 2021). El estrés también fue uno de los impactos psicológicos mayormente referidos, esto puede deberse a que cuando las personas están pasando por situaciones estresantes buscan apoyo emocional y social a través de las redes sociales y el teléfono inteligente es una forma rápida de poder buscar dicho apoyo, sin embargo, el buscar dicho apoyo y no encontrarlo también puede ser un foco de estrés (Dissing et al, 2019).…”
Section: Discussionunclassified
“…La multiplicación de los sitios de redes sociales ha llevado a una mayor frecuencia de uso entre los adultos jóvenes (Newman et al, 2021;Wojdan et al, 2021). Si bien la asociación con el bienestar mental sigue siendo controvertida, los altos niveles de uso de las redes sociales se correlacionaron con comportamientos problemáticos, baja autoestima y síntomas depresivos (El-Khoury et al, 2021).…”
Section: Introductionunclassified